Penatalaksanaan Fisioterapi pada Kasus Hemipharase Sinistra Pasca Stroke di RSUD Grati Pasuruan: Studi Kasus - Fitkiyah Nurul Khuzaimah; Safun Rahmanto; Tanti Kurniawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Stroke is a cerebrovascular disorder that disrupts blood flow and oxygen supply to the brain, leading to tissue damage and impaired function. This study examines the impact of physiotherapy interventions, including Neuromuscular Electrical Stimulation (NMES), stretching, strengthening, and ankle exercises, on a 60-year-old patient with hemiparesis sinistra post-stroke. The patient presented with abnormal gait, postural imbalance, and weakness in the left upper and lower limbs. After undergoing physiotherapy sessions twice a week for two weeks, the patient demonstrated increased muscle strength in the left lower extremity, reduced edema in the left leg, and improved range of motion, particularly in the hip and knee joints. These findings highlight the effectiveness of physiotherapy in enhancing functional recovery for post-stroke patients with hemiparesis sinistra.